Infantile haemangiomas that failed treatment with propranolol: Clinical and histopathological features. (6th June 2014) - Phillips, Roderic J; Lokmic, Zerina; Crock, Catherine M; Penington, Anthony
<x xml:space="preserve">Abstract</x> Aim To describe the clinical and histopathological characteristics of infantile haemangiomas that failed treatment with oral propranolol . Design This study is a case series from the vascular birthmarks clinic at Royal Children's Hospital, Melbourne. Patients The patients for this study were infants who commenced treatment with oral propranolol before 6 months of age and who were treated for at least 4 months without a satisfactory result. For histology and immunohistochemistry, tissue from the four non‐responding patients who subsequently underwent surgical excision was matched with four historical controls. Outcome measures Based on medical record review and photographic assessments, infants were defined as having failed treatment with oral propranolol if the infantile haemangioma either continued to grow or showed 20% improvement or less. Tissue sections were examined for tissue structure, mast cells, sympathetic innervations and beta‐2 adrenergic receptor expression, and the number of mast cells and beta‐2 adrenergic positive cells. Results From a group of 135 infants who met the inclusion criteria, 14 infants failed propranolol treatment. Eleven of these infants had focal facial haemangiomas. No difference was seen in tissue morphology, tissue innervations, beta‐2 adrenergic receptor expression, cell number or mast cell distribution, and number between non‐responding and control haemangiomas. Conclusion We report a treatment failure rate of 10%, which is higher than previously reported. Focal facial lesions failed to respond twice as frequently as other types of haemangioma. No histopathological reason was identified to indicate why some haemangiomas failed to respond.